Effects of congruity on the state of user presence in virtual environments: Results from a breaching experiment - Cahill, Tiernan J.; Cummings, James J. (Frontiers in Virtual Reality, 2023)
The present study investigates how the user state of presence is affected by contingencies in the design of virtual environments. The theoretical framework of congruity is herein explicated, which builds upon the concept of plausibility illusion as one of the essential prerequisites for presence, for systematically explaining and predicting presence in terms of alignment between schemata in the user's memory and stimuli presented within the virtual environment. Three dimensions of congruity are explicated and discussed: sensory, environmental, and thematic. A series of breaching experiments were conducted in a virtual environment testing the effects of each dimension of incongruity on presence. These experiments were inconclusive regarding the effects of sensory and environmental congruity; however, the results strongly suggest that the state of presence is contingent upon thematic congruity in virtual environments. This finding has theoretical significance insofar as it points towards the necessity of considering genre and cultural context in predicting user states in virtual environments. The study also has practical relevance to designers and developers of content for virtual reality in that it identifies a critical psychological consideration for the user experience that is absent from existing models.